Removal of Mercury from Coal-Fired Flue Gas and Its Sulfur Tolerance Characteristics by Mn, Ce Modified γ-Al2O3 Catalyst. (3rd August 2020) - He, Zhong; Xie, Yating; Wang, Yuan; Xu, Jingjie; Hu, Jiangjun
Abstract : Mercury pollution in the atmospheric environment is a matter of international concern. Mercury in coal-fired flue gas is the first human mercury emission source and has become the focus of national mercury pollution control. The catalytic performance of zerovalent mercury (Hg 0 ) in coal-fired flue gas was studied by using manganese-cerium-aluminum oxide as catalyst. The effects of metal loading ratio, reaction temperature, calcination temperature, and O2 and SO2 concentration on the efficiency of Hg 0 catalytic removal were investigated, and the Mn-Ce/ γ -Al2 O3 catalysts before and after the reaction were characterized by BET, SEM, XRD, and XPS to analyze the physicochemical properties of the samples. The results show that the mercury removal efficiency of the composite catalyst with Mn, Ce, and Al as the active component is higher than that of the single metal catalyst. The catalytic activity of Mn0.1 Ce0.02 Al is the best, the optimum reaction temperature is 150°C, the optimum calcination temperature is 400°C, and the O2 concentration in the conventional flue gas condition satisfies the effective oxidation of Hg 0 ; SO2 in the flue gas can seriously inhibit the oxidation of Hg 0 .